2023
DOI: 10.3389/fpsyg.2023.1207199
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acute exercise on objectively measured sleep and cognition in older adults

Kelsey R. Sewell,
Nathan D. W. Smith,
Stephanie R. Rainey-Smith
et al.

Abstract: BackgroundExercise can improve cognition in aging, however it is unclear how exercise influences cognition, and sleep may partially explain this association. The current study aimed to investigate whether objectively measured sleep mediates the effect of an acute exercise intervention on cognition in older adults.MethodsParticipants were 30 cognitively unimpaired, physically active older adults (69.2 ± 4.3 years) with poor sleep (determined via self-report). After a triple baseline cognitive assessment to acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The uniqueness of our findings lies in the fact that a single 20-min session of moderate-intensity physical exercise can yield a beneficial effect, similarly in males and females. Notably, this association between exercise (specifically, 20 min of moderate-intensity pedalling) and cognition holds promise, especially when contrasted with the findings of the study by Sewell et al ( 20 ), which showed no immediate positive effect of a 20-min high-intensity pedalling exercise on cognition in older adults. This finding suggests that, particularly for older individuals, moderate exercise may provide greater cognitive benefits compared to high-intensity exercise.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The uniqueness of our findings lies in the fact that a single 20-min session of moderate-intensity physical exercise can yield a beneficial effect, similarly in males and females. Notably, this association between exercise (specifically, 20 min of moderate-intensity pedalling) and cognition holds promise, especially when contrasted with the findings of the study by Sewell et al ( 20 ), which showed no immediate positive effect of a 20-min high-intensity pedalling exercise on cognition in older adults. This finding suggests that, particularly for older individuals, moderate exercise may provide greater cognitive benefits compared to high-intensity exercise.…”
Section: Discussionmentioning
confidence: 69%
“…Conversely, Hubner et al ( 19 ) found no significant benefits on learning consolidation or acquisition immediately after an acute bout of moderate-intensity exercise when compared to controls who did not exercise. Similarly, a recent study by Sewell et al ( 20 ) showed no significant effect on cognition after 20 min of acute exercise at moderate intensity in older adults. While there's substantial evidence to suggest that an acute bout of physical exercise can enhance cognitive performance, the optimal exercise characteristics (e.g., exercise intensity and exercise type) remain elusive.…”
Section: Introductionmentioning
confidence: 71%